Efficacy of Intra-Arterial Plus Intravesical Chemotherapy for High-Risk Non-Muscle-Invasive Bladder Cancer: A Pooled Analysis - Cheng, Chunliang; Qiu, Dongxu; Chen, Jinbo; Zu, Xiongbing; Liu, Jinhui; Li, Huihuang; Hu, Jiao; Yi, Zhenglin; He, Tongchen; Chen, Zhi; Cui, Yu (Frontiers in Pharmacology, 2021)
Abstract Background: The treatment for high-risk non-muscle-invasive bladder cancer (NMIBC) remains highly debated for its high recurrence and progression risk. This work aimed to verify the efficacy and toxicity of intra-arterial chemotherapy (IAC) plus intravesical chemotherapy (IVC) in high-risk NMIBC. Methods: A comprehensive online literature search was conducted in three databases to select researches related to IAC+IVC for high-risk NMIBC. All data were analyzed using the Review Manager software version 5.3. And we used the Cochrane Risk of Bias tool to assessed the quality of these enrolled researches. Results: Seven eligible original publications were enrolled in our studies with a total of 1247 patients. Compared with the intravesical instillation, IAC+IVC therapy showed a better therapeutic effect. The total odds ratio for tumor recurrence rate, tumor progression rate, survival rate, and tumor-specific death rate was calculated as 0.51 (95% CI: 0.36–0.72; P<0.05), 0.51 (95% CI: 0.36–0.72; P<0.05), 1.75 (95% CI: 1.09–2.81; P<0.05), and 0.48 (95% CI: 0.28–0.84; P<0.05) respectively. In patients who received IAC, most of the adverse events (AEs）in the treatment were Grade I and II. Conclusion: IAC+IVC regimen for high-risk NMIBC could effectively reduce recurrence and progression and provide a better prognosis than intravesical instillation. The adverse events of IAC were mild and acceptable.